Türk Milli Eğitim Sisteminde Yeni Bir Okul Kütüphanesi Türü: Sıfır Atık Kütüphaneleri Üzerine Bir Değerlendirme - DALKIRAN, Ömer; DALKIRAN, Ömer (İstanbul Medeniyet Üniversitesi, 2023)
Recently, news about the efforts to establish libraries in schools affiliated to the Ministry of National Education have been brought to agenda. Libraries that have been established with the aid of recyclable materials are the emphasis of these news items. It is stated that these efforts will continue systematically and these libraries will also be expanded. With these libraries called Zero Waste Libraries or Recycling Libraries, it is seen that a kind of library, almost a new model, is deployed in the Turkish National Education System. In this framework, it would be useful to scrutinize the Zero Waste Libraries Initiative/Project and to reveal the quality of the libraries established within this scope along with a systematic and organized approach, clearly. In this direction, the aim of the research is to analyze the Zero Waste Libraries Project carried out by the Ministry of National Education in general terms. The main analysis is largely carried out in the context of the written news content of the public websites in the first 10 pages of the Google Search Engine. These contents were analyzed and evaluated through document analysis. The findings show that the Project was initiated with an arbitrary process, and without getting opinions and support of the Information and Records Management/Librarianship community. It is understood that the "libraries" established within the framework of the project essentially consisted of placing bookshelves and donated books in some places in schools. Moreover, no school librarian is assigned to these libraries. In general, although the Project and its results are very useful in terms of raising zero waste awareness among students, it presents an inadequate, unqualified and even negative view of the library institution in terms of scientific librarianship principles. It is considered that the places described as Zero Waste Libraries should not be accepted as school libraries in their current state.

Son dönemde basında Milli Eğitim Bakanlığı’na bağlı okullarda kütüphane kurma çalışmaları ile ilgili haberler gündeme gelmektedir. Bu haberlerde okullarda geri dönüştürülebilir atık malzemelerden kütüphaneler kurulduğu vurgulanmaktadır. Bu yöndeki çalışmaların sistematik biçimde devam edeceği ve bu kütüphanelerin yaygınlaştırılacağı da ifade edilmektedir. Sıfır Atık Kütüphanesi veya Geri Dönüşüm Kütüphanesi olarak adlandırılan bu kütüphaneler ile Türk Milli Eğitim Sisteminde adeta yeni bir tür kütüphane modelinin konumlandırıldığı görülmektedir. Bu çerçevede Sıfır Atık Kütüphaneleri Girişimini/Projesini mercek altına alarak bu kapsamda kurulan kütüphanelerin niteliğinin sistemli ve düzenli bir yaklaşımla açıkça ortaya konulması yararlı olacaktır. Bu istikamette araştırmanın amacı Milli Eğitim Bakanlığı’nın yürüttüğü Sıfır Atık Kütüphaneleri Projesi’ni genel çizgileriyle analiz etmektir. Temel analiz çok büyük oranda Google arama motorundaki sorgulama sonuçlarıyla ulaşılan ilk 10 sayfadaki kamu sitelerinin yazılı haber içerikleri bağlamında gerçekleştirilmektedir. Bu içerikler doküman analizi yoluyla incelenmiş ve değerlendirilmiştir. Bulgular, Projenin Bilgi ve Belge Yönetimi/Kütüphanecilik topluluğunun fikir ve desteği alınmaksızın plansız bir süreçle başlatıldığını göstermektedir. Proje çerçevesinde kurulan “kütüphane”lerin özünde okullardaki bazı mekânlara kitap rafı ve bağış kitapların konulmasından ibaret olduğu anlaşılmaktadır. Ayrıca, buralarda okul kütüphanecisi görevlendirilmemektedir. Genel olarak Proje ve sonuçları öğrencilere sıfır atık bilinci kazandırma açısından oldukça yararlı bulunsa da bilimsel kütüphanecilik ilkeleri açısından kütüphane kurumuna yetersiz, niteliksiz ve hatta olumsuz bir bakış sunmaktadır. Sıfır Atık Kütüphanesi olarak nitelendirilen mekânların mevcut haliyle okul kütüphanesi olarak kabul edilmemesi gerektiği değerlendirilmektedir.
Keywords: Library and Information Studies; Okul kütüphanesi; Sıfır Atık Kütüphanesi; Geri Dönüşüm Kütüphanesi; Türkiye; School library; Zera Waste Library; Recycling Library; Kütüphane ve Bilgi Çalışmaları; 4. Education; 12. Responsible consumption